The Role of Affiliate Marketing Content in Influencing Purchasing Decisions at TikTok Shop: A Study of Bandar Lampung Community - Thalia Sajidah Natasya; Bartoven Vivit Nurdin; Guntur; Usman Raidar (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
The public consumption process is starting to change, especially in online purchasing behaviour, where a TikTok Shop feature makes it easier for users to buy directly. However, there are complaints about the incompatibility of products with existing promotional content, which is a gap between the information users receive. This results in diminished trust in the information found on social media, leading to a decline in purchasing decisions. This study aims to determine how much affiliate marketing content influences improving users' purchase decisions. This study uses quantitative methods. Data was collected using questionnaires. The data analysis method uses simple linear regression analaysis by performing clasiccal assumption testing using SPSS 25 for windows. The study respondents were 110 TikTok Shop users. The Content Marketing Affiliate study results can positively and significantly influence purchasing decisions on TikTok Shop, where the beta T test value is 0,081. Only 17,2% of the variation shows that other unexplored factors are present. This research aims to help affiliates focus on honest and informative content quality. As well as contributing to the development of media sociology theory.